Characterisation of crude and partially purified peptides with antimicrobial activity from the skin of Bornean frogs - Mardhiah, Mohd Shahabuddin; Muna, Sabri; Ramlah, Zainudin; Ahmad Hata, Rasit (UMT, 2018)
Antimicrobial peptides are one of the most promising antibiotic candidates with the effectiveness in killing the microorganisms, can be found largely in the frog skin. In this study, the antimicrobial properties of the crude and partially purified peptides from the frog skin of Bornean frogs; Chalcorana raniceps, Limnonectes kuhlii, Meristogenys jerboa, Odorrana hosii, Staurois guttatus and Limnonectes leporinus were determined. Crude peptides from the skins of these frogs were partially purified using C18 Sep Pak columns. The antimicrobial activities tested were disc diffusion, minimum inhibitory concentration and minimum bactericidal concentration test. L. leporinus and L. kuhlii peptides displayed the lowest MIC value against P. aeruginosa (62.5 µg/ mL) and S. typhimurium (125 µg/mL). Moreover, L. leporinus peptide showed the lowest MIC value against S. aureus (31.25 µg/mL). Both L. kuhlii and L. leporinus peptides share the lowest MBC value of 125 µg/mL against S. aureus and P. aeruginosa. Peptides from L. kuhlii exhibited the lowest MBC values against MRSA (125 µg/mL), E. coli (62.5 µg/mL) and S. typhimurium (125 µg/mL). It can be concluded that all extracted skin peptides have antimicrobial activity against the selected bacteria, with the skin peptides from L. kuhlii and L. leporinus frogs being more potent than other species studied. The antimicrobial characteristics of peptide samples imply that there is a potential of novel AMPs from the frog species of Borneo. For future study, the peptides of frog skin extracts should be further purified.